P19 contributes to Mycoplasma mycoides subsp. mycoides adhesion to EBL cells. (April 2016) - Zhou, Yumei; Wang, Yang; Li, Yuan; Nick, Nwankpa; Zou, Xiaohui; Bai, Fan; Wu, Jindi; Xin, Jiuqing
Abstract: Mycoplasma mycoides subsp. mycoides (Mmm) is the causative agent of contagious bovine pleuropneumonia (CBPP). The virulent Mmm Ben-1 strain was isolated from the lung of a CBPP-infected cow in China in the 1950s. To attenuate the virulence of the Ben-1 strain and preserve its protective ability, the isolate was re-isolated after inoculation into the testicles of rabbits and into the rabbit thorax. As a result, after the subsequent isolates were continuously passaged 468 times in rabbits, its pathogenicity to cattle decreased. However, the molecular mechanisms leading to attenuation of the Mmm Ben-1 remain unknown. We compared the entire genomes of the Ben-1 strain and the 468th generation strain passaged in rabbits (Ben-468) and discovered that a putative protein gene named p19 was absent from the Ben-468 strain. The p19 gene was cloned and expressed in Escherichia coli to obtain recombinant P19 (rP19). Western blot analysis demonstrated that the P19 protein is detected in the cell-membrane fraction, the cell-soluble cytosolic fraction and whole-cell lysate of the Mmm Ben-1 strain. The rP19 can interact with international standard serum against CBPP. Immunostaining visualised via confocal laser scanning microscopy indicated that P19 is able to adhere to embryonic bovine lung (EBL) cells, and this finding was also confirmed by a sandwich ELISA. We also found that anti-rP19 serum could inhibit the adhesion of the Mmm Ben-1 total proteins to EBL cells. Highlights: P19 exists in Mmm Ben-1 strain. P19 does not exist in Mmm Ben-468 strain. P19 contributes to Mmm Ben-1 adhesion to Embryonic bovine lung (EBL) cells.